The Generation and Development of Metaphoric Lexical Meanings of “Brat” from the Perspective of the Working Hypothesis of the Cactus Model - Zhu Shuangjie; Yang Tangfeng (International Journal of Education and Humanities, 2025)
This academic investigation employs Wang Wenbin's Cactus Model of Metaphorical Semantic Change to trace the diachronic development of the lexical item brat. Drawing upon corpus evidence from the Corpus of Contemporary American English spanning three decades, the study identifies four distinct semantic interpretations: an ill-mannered child; offspring within professional or military communities; a largely obsolete term for aprons or overalls; and a contemporary descriptor for individuals exhibiting confidence, independence, and hedonism. Analysis reveals a non-linear evolutionary trajectory progressing from textile-related origins through behavioral associations to sociocultural conceptualizations. The metaphorical mechanisms underpinning this transformation are critically examined. The initial semantic shift occurred through physical resemblance, linking fabric artifacts to child behavior. Subsequent transitions leveraged psychological parallels, connecting behavioral traits to social identity within privileged groups. Most notably, the emergence of the modern connotation reflects sociocultural recontextualization, where notions of privilege were abstracted into expressions of individualism under shifting cultural values. The Cactus Model effectively illustrates these dynamics, demonstrating how semantic nodes interrelate through overlapping attributes while remaining rooted in cultural contexts. Findings confirm that lexical evolution is fundamentally driven by cognitive similarity operating within specific cultural milieus. Each semantic stage retains core attributes while developing distinctive identities, validating the model’s capacity to map how meanings dynamically expand through metaphor. The study highlights the inseparability of linguistic change from its sociocultural ecosystem, demonstrating the explanatory power of the Cactus framework for lexical semantics